PERJANJIAN KAWIN SEBAGAI PERLINDUNGAN HUKUM BAGI PEREMPUAN (LOKASI: KELURAHAN TANJUNG SELAMAT, MEDAN TUNTUNGAN) - Rosnidar Sembiring; Zulfi Chairi; Rabiatul Syariah (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
People still understand the marriage agreement in a negative way. The reason due to the big theme of the content of a marriage agreement is wealth, both innate property and property acquired during the marriage. Based on the above, this paper wants to discuss how the public's understanding of the marriage agreement? and second, what are thesociety's reasons for accepting or rejecting the application of the marriage agreement in their domestic life? This research uses a normative juridical research with a descriptive analytical approach. The results show that people still do not fully understand the function of making a marriage agreement in married life. The things that become the basis for refusing the application of marriage agreements by some people are divided into 2, namely first, because the word agreement is synonymous with business activities such as trading, buying and selling, and so on. So how can something as sacred as marriage be considered like a business activity? Second, wealth is a big theme that is regulated in the marriage agreement. This is considered unethical and materialistic by some people and families in Indonesian culture.